A novel approach to the sustainable financing of the global restoration of degraded agricultural land. (19th December 2019) - Chapman, Bruce; Lindenmayer, David B
Abstract: Humanity must find ways to feed an expanding human population. This requires maintaining the productivity of agricultural land, although much of it is increasingly degraded. Many trillions of dollars will be needed to address land degradation globally, but there has been little discussion about how to sustainably finance major global initiatives such as the UN Decade of ecosystem restoration. We suggest that existing financing instruments (government grants and commercial loans) have two limitations. First, the size of the problem is so substantial that contemporary approaches have no real prospects of adequately addressing the issue. Second, even if grants and loans had the potential in terms of prospective magnitude, in many instances they would be inequitable, regressive and/or have high risks for farm properties. We examine an alternate financing instrument, revenue-contingent loans (RCL), which potentially has subsidy-reducing properties for government budgets, and thus the capacity for more broadly-based public sector engagement with agricultural land remediation. RCL can substantially diminish borrowing risks and hardship for farm properties. Unlike commercial debt, repayments under RCL are not time-based but instead occur when a farm business can afford to make them. This is important as remediation of farmland degradation can be a medium to long-term process, and hence loan repayments need to parallel the time that it takes for the benefits of restoration to accrue to a farm business. Using income data from Australian agriculture, we illustrate empirically the repayment effects of a hypothetical RCL, focusing on the consequences for a government's budget, the time stream of repayments for farms differing in revenue streams, and the benefits of income-smoothing. Our results underscore the potential benefits of RCL for the financing of land restoration investments, for both farmers and taxpayers. RCL could be made operational without significant costs to government budgets and within acceptable time frames.